PENGUKURAN TINGKAT PELAYANAN TATA KELOLA TEKNOLOGI INFORMASI DENGAN MENGGUANAKN DOMAIN ME ( MONITORNG AND EVALUATION ) PADA KERANGKA KERJA COBIT 4.0 (Studi Kasus : Digibook, Jakarta) - Sandra Jamu Kuryanti (Universitas Bina Sarana Informatika, 2014)
Good IT management application of information technology is expected to run optimally . IT management is best done by assessing the suitability anatara application of IT and business processes of the organization. With the increasing use of IT in business , IT governance becomes important concepts discussed . IT governance information system services to customers in digibook been done although still not running optimally because they have not reached the expected level of maturity . Analysis was conducted to determine the maturity level of IT governance maturity level based on the condition of governance institutions currently obtained through questionnaire , interview and observation in accordance with the standards set by COBIT. Analysis maturity level is done by processing the results of the questionnaire respondents maturity models . Questionnaire design is done by providing a number of questions for each level of control objectives that exist in the Domain Monitoring and Evaluation ( ME ) . The level of maturity ( Maturity Level ) that exist in every domain of IT processes contained in the monitor and Evaluate ( ME ) on average 3,246 and still be at level 3 ( defined process).Keywords: COBIT , Monitoring and Evaluation ( ME ) , IT Governance